(untitled) (Iranian Journal of Kidney Diseases, 2020)
Bartter’s syndrome is a rare disorder usually presenting antenatal or in childhood and is characterized by hypokalemia, metabolic alkalosis, hyperaldosteronism and normal blood pressure. We report a case of adult-onset Bartter’s syndrome in a 38 year old male who presented with lower limb weakness.